角色楷模課程對高中數理資優女生性別角色、生涯自我效能與生涯發展影響之研究 The Effects of a Mentoring Curriculum on Gender Roles, Career Self-Efficacy, and Career Development in a High School Class for Gifted Girls in Math and Science - 于曉平 Hsiao-Ping Yu (Journal of Research in Education Sciences, 2010)
本研究探討角色楷模課程之實施對高中數理資優女生性別角色、生涯自我效能與其生涯發展的影響，並嘗試進行理論的驗證。本研究以自編的角色楷模課程進行教學實驗，並以自編之「高中女生性別角色與發展量表」進行施測，嘗試透過角色楷模課程的介入，瞭解其對數理資優女生性別角色、生涯自我效能與其生涯發展的影響與變化，透過22 週的課程後調查與追蹤發現，角色楷模課程對數理資優女生性別角色、生涯自我效能與生涯發展雖有所提升，但並無顯著影響，不過從學生課程中所寫之心得分析發現，角色楷模課程對學生性別角色態度的覺知、生涯自我效能的提升與生涯發展方向的確認與瞭解都有正向的幫助，之後並進行追蹤瞭解後續的影響。此外，配合Bandura（1977）所提出之自我效能理論加以驗證，以瞭解成就、角色楷模、情緒、支持與生涯自我效能的關聯，並提出教育與研究上的建議。 This study examined a mentoring curriculum to understand its influences on gender roles, career self-efficacy, and career development choices in adolescent girls who were students in a senior high school class for gifted students in math and science. After the 22-week curriculum, it found that the mentoring didn’t have a significant influence on the girls’ gender roles, career self-efficacy, or career development. However students indicated that the curriculum helped them to be more aware of gender roles, and they better knew how to promote career self-efficacy, and to better plan their future career development. Techniques taught in the curriculum to improve self-efficacy were viewed as beneficial. According to the above findings, there were some suggestions proposed for readers.